Building cultural intelligence: insights from project management job advertisements. Issue 3 (17th February 2016) - Chipulu, Maxwell; Ojiako, Udechukwu; Marshall, Alasdair; Williams, Terry; Neoh, Jun Guan; Mota, Caroline; Shou, Yongyi
Abstract: This paper examines how organisations that conduct worldwide recruitment of project management professionals can derive insight from the cultural preferences stated within project management job advertisements. Drawing on project management practitioner job advertisements placed by 2040 organisations across seven countries and seven industries, we employ Hofstede's national cultural framework to categorise cultural preferences which the organisations persistently replicate in their specifications of desired candidate project management practitioner competency. To map global trends and national variations, data analysis is undertaking and utilising exploratory data analysis, Poisson regression and negative binomial regression are used. The paper finds that specific national cultural dimensions – 'Collectivism', 'Uncertainty Avoidance' and, to a lesser extent, 'Power Distance' – are the most salient cultural denominators for advertised project management positions, while this is not the case with 'Masculinity' and 'Individualism'. The findings raise issues about which organisations should seek to become more culturally intelligent, and which relate to the adaptiveness of the cultural preferences that they articulate through their job advertisements, both to project tasks and to cultural contexts for projects.